A polynuclear Cu(ii) complex for real time monitoring of mitochondrial cytochrome C release during cellular apoptosis. Issue 48 (12th May 2020) - Khanra, Somnath; Ta, Sabyasachi; Paladhi, Ankush; Ghosh, Milan; Ghosh, Subhasis; Hira, Sumit Kumar; Manna, Partha Partim; Brandão, Paula; Félix, Vítor; Das, Debasis
Abstract : Single crystal X-ray structurally characterized poly-nuclear Cu(ii ) complex (M1) selectively and spatially interacts with Cytochrome C (Cyt C ) to allow fluorescence imaging of intracellular translocation events in live cells during apoptotic process. Abstract : A new amide–imine conjugate, 2-hydroxybenzoic acid-(2-hydroxybenzylidene)-hydrazide (L1 ), is employed to prepare a single crystal X-ray structurally characterized poly-nuclear Cu(ii ) complex (M1). M1 selectively and spatially interacts with cytochrome C (Cyt C ) to allow fluorescence imaging of intracellular translocation events in living cells. Thus, direct visualization of a Cyt C translocation event during an apoptotic process is achieved for the first time. The binding constant and LOD are 7.52 × 10 4 M −1 and 34.0 nM, respectively.